Case report: Envafolimab combined with Endostar in the treatment of advanced non-small cell lung cancer with malignant pleural effusion - Dong, Changhong; Hu, Chenxi; Jiang, Yanting; Hui, Kaiyuan; Jiang, Xiaodong (Frontiers in Oncology, 2024)
Malignant pleural effusion (MPE) is one of the common complications of lung cancer. The quality of life and prognoses for MPE patients are significantly compromised. Controlling the production of MPE can relieve patients’ symptoms, improve their quality of life, and prolong their survival. This article presents a case of advanced non-small cell lung cancer (NSCLC) with MPE and negative driver genes. The patient received envafolimab and Endostar in combination, resulting in a complete reduction of MPE and durable clinical benefits. The exploratory use of this treatment method improved the quality of life of this patient and has the potential to prolong the survival of this patient.